2020
DOI: 10.1186/s43014-020-00043-9
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and purification of ustiloxin A from rice false smut balls by a combination of macroporous resin and high-speed countercurrent chromatography

Abstract: Rice false smut is an emerging plant disease worldwide. Ustiloxin A (UstA) is the major mycotoxin found in rice false smut balls, which are fungal colonies in rice florets. In this study, a new method consisting of macroporous resin column chromatography and high-speed countercurrent chromatography (HSCCC) was developed for UstA separation. UstA was extracted by a 3.81% HCOOH solution and adsorbed by XAD-4 resin. UstA was then eluted by a 40% methanol solution supplemented with 0.1% trifluoroacetic acid (TFA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…These results could be attributed to the high sensitivity of ustiloxins D and F on the LC-MS/MS instrument. Our findings are consistent with previous studies, which reported that ustiloxin A was the major and common ustiloxin in rice grain and false smut balls [19,37]. According to our results, the contamination of ustiloxins in rice from southern China is widespread and severe.…”
Section: The Occurrence Of Ustiloxins In Paddy Samplessupporting
confidence: 93%
“…These results could be attributed to the high sensitivity of ustiloxins D and F on the LC-MS/MS instrument. Our findings are consistent with previous studies, which reported that ustiloxin A was the major and common ustiloxin in rice grain and false smut balls [19,37]. According to our results, the contamination of ustiloxins in rice from southern China is widespread and severe.…”
Section: The Occurrence Of Ustiloxins In Paddy Samplessupporting
confidence: 93%